Folate receptor β performs an immune checkpoint function in activated macrophages - Zhang, Fenghua; Al-Amin, Md Yusuf; Utturkar, Sagar; Jiang, Rina; Cresswell, Gregory; Alfar, Rami; Ophaug-Johansen, Ian; Bachman, Gabriel; Srinivasarao, Madduri; Finnell, Richard; Puig-Kröger, Amaya; Ratliff, Timothy; et al. (Frontiers in Immunology, 2025)
Monocytes and macrophages are sentinels of the immune system that distinguish themselves from other cells by expressing the beta isoform of the folate receptor (FRβ). Because FRβ does not bind folate until the monocyte/macrophage is exposed to immunosuppressive cytokines, the question naturally arose whether FRβ might also perform an immune-related function. To examine this matter, we compared the properties of wild type (WT) and FRβ knockout mice. We observe that FRβ knockout (KO) mice display autoimmune symptoms that can include alopecia, enlarged spleens, and dermatitis, despite having normal cellular folate levels. We further demonstrate that syngeneic tumors (TRAMP C2, MC38) grow much slower in FRβ KO mice than wildtype mice. Comparison of cells extracted from syngeneic tumors of KO mice further reveal that CD69+ T cells are increased while PD1+ T cells and PD-L1+ myeloid cells are decreased in KO tumors. More detailed comparison of the bone marrow-derived macrophages from KO and WT mice demonstrates that KO mice have upregulated pro-inflammatory genes and downregulated anti-inflammatory genes. Because blockade of FRβ with a monoclonal antibody or deletion of FRβ impairs direct macrophage suppression of T cell activation in vitro, we conclude that FRβ performs a checkpoint function that regulates the immunologic properties of tumor myeloid cells. Since FRβ expression in human cancers is shown to correlate inversely with overall survival, we further posit that FRβ similarly performs an immunosuppressive function in human tumors.